GENTAS (Gerakan Tuntas Stroke): Sosialisasi Hidup Aktif dan Deteksi Dini untuk Usia Produktif dan Lansia di Wonogiri - Muhamad Fathir Firdaus; Lilik Ariyanti; Anggun Marlinda Nur Alkarin; Muhammad Danish Raqilla; Prita Putri Setyawan; Ratu Julyeta Eka Mahesti (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Stroke is one of the leading causes of death and disability in Indonesia. Limited public knowledge regarding risk factors, early detection, and healthy lifestyles contributes to the increasing risk of stroke. This community service program aimed to improve public knowledge of stroke prevention through active lifestyle education and early detection in Wonokerto Village, Wonogiri Regency. The methods included health education, interactive discussions, stroke prevention exercise demonstrations, health examinations, and questionnaire-based evaluations. A total of 15 participants attended the program. The results showed improved participants' knowledge of early stroke management and the importance of adopting an active lifestyle. All participants were willing to perform stroke prevention exercises at home, while 93.3% committed to regular stretching and walking. The GENTAS program effectively increased community knowledge and encouraged preventive behaviors to reduce stroke risk.